Optimizing the Function of the House of Representatives in Overseeing the Government in the Digital Government Era - Mohammad Fajar Abdjul (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The shift towards digital governance has triggered major transformations in public administration, particularly in how oversight is conducted by the Indonesian House of Representatives (DPR). The era of digital government is characterized by the adoption of the Electronic-Based Government System (SPBE), which enables electronic data storage, processing, and dissemination. This digital infrastructure offers a significant opportunity for the DPR to enhance its supervisory role through faster, more transparent, and traceable access to government data. However, several challenges persist, including limited access to internal government data, risks of digital information manipulation, and the relatively low level of digital literacy among some legislative members. This study employs a qualitative-descriptive approach to explore these dynamics, with a focus on the DPR’s oversight of digital education funding during the Covid-19 pandemic. The findings reveal that effective parliamentary oversight requires not only open data systems and improved digital competencies among legislators but also active collaboration with civil society. The case of monitoring internet quota assistance and digital infrastructure in underdeveloped, frontier, and outermost (3T) regions illustrates the importance of data-driven and adaptive oversight in formulating responsive public policies. In conclusion, as bureaucracy undergoes digital transformation, strengthening the DPR’s oversight capacity is essential to uphold government transparency and accountability.